Risk assessment of mycotoxins, the identification and environmental influence on toxin-producing ability of Alternaria alternate in the main Tibetan Plateau Triticeae crops - Wang, Jun; Zhang, Feilong; Yao, Ting; Li, Ying; Wei, Na (Frontiers in Microbiology, 2023)
In order to find out the contamination of mycotoxins in Triticeae crops of Qinghai-Tibet Plateau, a total of 153 Triticeae crop fruits were collected as target samples, and 22 mycotoxins were tested. High detection rate was found in the Alternaria mycotoxins, including tentoxin (TEN), tenuazonic acid (TEA)and alternariol (AOH)toxins. To further clarify the production rules of Alternaria mycotoxins. A number of 9 high yield toxic strains were selected from 65 bacterial strains and the gene sequences of each were determined. The 9 selected Alternaria alternate were cultured under specific pH of the culture medium, temperature and ultraviolet (UV)irradiation, and their growth and toxicity were analyzed. The results showed that the toxic capacity of most Alternaria alternate increased with the increase of culture environment temperature and decreased with the increase of UV irradiation. However, the production of some toxins did not meet this principle, or even met the principle of relativity. In the culture experiments, a total of 5 Alternaria toxins were detected as positive, which were TEN, AOH, alternariol monomethyl ether (AME), TEA, and Alternaria (ALT). The altenusin (ALS)toxin was not detected in the metabolites of the 9 Alternaria strains. It indicated that the TEN, AOH, AME, TEA, and ALT toxins should be particularly valued in the future risk assessments. This finding provided comprehensive information of mycotoxins contamination in the Tibetan Plateau Triticeae crops, it pointed out a direction to the Tibetan Plateau food crops’ quality control.